Nicotinamide Riboside Improves Cardiac Function and Prolongs Survival After Disruption of the Cardiomyocyte Clock - Dierickx, Pieterjan; Carpenter, Bryce J.; Celwyn, Isaac; Kelly, Daniel P.; Baur, Joseph A.; Lazar, Mitchell A. (Frontiers in Molecular Medicine, 2022)
The REV-ERB nuclear receptors are key components of the circadian clock. Loss of REV-ERBs in the mouse heart causes dilated cardiomyopathy and premature lethality. This is associated with a marked reduction in NAD+ production, but whether this plays a role in the pathophysiology of this heart failure model is not known. Here, we show that boosting NAD+ levels with a dietary supplement improves heart function and extends the lifespan of female mice lacking cardiac REV-ERBs. Thus, boosting NAD+ levels can improve cardiac function in a setting of heart failure caused by disruption of circadian clock factors, providing new insights into the links between the circadian clock, energy metabolism, and cardiac function.